Collagen-based and high-transparency matrix for cornea thickening and preparation method of collagen-based and high-transparency matrix
Highly transparent collagen matrix implants were prepared through electrochemical deposition assembly technology and equipped with nerve growth factors, which solved the myopia or astigmatism problems and the difficulty of nerve repair after implantation of the corneal stromal ring, achieved high light translucency and nerve regeneration of the cornea, and reduced the risk of secondary surgery.
Patent Information
- Application Number
- CN202411791503.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, in the treatment of keratoconus and traumatic corneal injury, myopia or astigmatism still exists after implanting the corneal stromal ring, and the damaged neural tissue is difficult to repair itself, resulting in worsening vision and risk of secondary surgery.
Electrochemical deposition assembly technology is used to prepare highly transparent collagen matrix implants. The arrangement of collagen assembled fibers is controlled through electric field energy regulation, which increases light transmittance, and is equipped with nerve growth factor (NGF) in the implants to promote nerve repair.
The high light transmittance of the cornea is achieved, the regeneration of the nerve fibers of the corneal stromal is promoted, the stable maintenance of the thickness of the corneal stromal is extended, the risk of secondary surgery is reduced, and the postoperative recovery effect is improved.
Smart Images

Figure CN119587759A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biomedical materials, and in particular to a collagen-based and highly transparent matrix for corneal thickening and a preparation method thereof. Background Art
[0002] Corneal disease is one of the three major blinding eye diseases in the world. There are 60 million patients blinded by corneal disease worldwide, of which about 4 million are in my country, ranking second among ophthalmic blinding diseases. Among them, keratoconus also accounts for a large proportion of corneal diseases. Keratoconus is an eye disease characterized by progressive protrusion of the central part of the cornea. Patients with keratoconus show irregular thinning of the central or paracentral cornea, and progressive vision loss with astigmatism. Frame glasses and corneal contact lenses are usually used for treatment in the early stage. As the disease progresses, patients will experience varying degrees of irreversible visual impairment. If the progression of the disease is not slowed down or stopped in time, about 20% of keratoconus patients will require corneal transplantation due to severe visual impairment. Corneal transplantation is the only treatment for corneal blindness, but due to the severe shortage of corneal donors, the number of corneal transplants in my country does not exceed 10,000 cases per year.
[0003] At present, the commonly used surgical methods for the clinical treatment of keratoconus or highly irregular myopic astigmatism caused by traumatic corneal injury include corneal collagen cross-linking, deep anterior lamellar or penetrating keratoplasty, anterior Descemet's membrane transplantation, and intrastromal corneal ring segments (ICRS) implantation, or a combination of two or even three. ICRS was first used to correct myopia, and is now more commonly used to treat diseases related to corneal ectasia. The implantation of corneal stromal rings can shorten the arc length of the central part of the cornea, flatten the central cornea, and reduce the refractive power, thereby achieving the purpose of treating axial myopia and irregular astigmatism. However, at the same time, the problems caused by the implantation of corneal stromal rings are: ① Since ICRS does not reduce the corneal curvature to the greatest extent, residual myopia or astigmatism will still occur after surgery; ② The damaged nerve tissue is difficult to self-repair in the later stage. Studies have found that after most corneal transplants, the nerves in the superficial stromal layer grow from the periphery to the center. The sensory nerve fibers caused by the corneal stromal ring are destroyed, resulting in a decrease in both the basal and reflex secretion of tears. The neurotrophic function of corneal epithelial cells is destroyed. At the same time, the ocular surface loses sensory nerve control, the lacrimal glands are dysfunctional, and symptoms such as ocular surface irritation occur, further aggravating vision deterioration.
[0004] In the research and application of corneal thickening materials, the patent (CN1460715A) discloses a corneal thickening implant, whose substrate is non-woven polyglycolic acid (PGA) fiber, and corneal stromal cells are implanted on the material, aiming to avoid complications such as corneal dissolution, aqueous humor leakage and implant dislocation that may be caused by transplantation of other alternative materials. However, its biocompatibility is not ideal, and it cannot quickly repair damaged stromal nerve tissue. The implant begins to gradually degrade after 8 weeks, and cannot continuously thicken the corneal stroma for a long time, resulting in surgical failure, so that patients need to bear the risk of secondary surgery and related medical expenses in the short term.
[0005] The patent (CN114618016A) provides an artificial cornea and a method for preparing the same. The method for preparing the artificial cornea includes designing a customized electrode and using a deposition method to prepare a collagen artificial cornea. The collagen-based artificial cornea material is characterized in that it is composed of collagen microfibers and has a certain degree of transparency. The production process of the invention does not require the use of complex equipment, and the obtained collagen-based artificial cornea material can be used to replace or repair the natural cornea, but it is mainly used for the repair of corneal lamellae and cannot be used for thickening the corneal stroma. At the same time, this technology uses glutaraldehyde cross-linking. If the cross-linking time is too long, the material will turn to brittleness, turn yellow and affect the transmittance, and the material will cause certain toxicity. It was learned from the animal experiment slices that the material has been basically degraded completely in the body for two months, which cannot meet the current clinical needs of artificial corneal stroma.
[0006] The patent (CN108601861A) uses a collagen gel to repair tissue defects, but when applied to the corneal stroma, its defect is that the in vitro degradation time is too fast, and the first and second cross-linked area materials are completely degraded within 18 hours, and there is a lack of animal corneal tissue as a control reference. Clinical experts agree that the material used for corneal stroma thickening needs to maintain corneal thickness for as long as possible. The patent invention content also lacks corresponding nerve repair-related efficacy characterization, and to a certain extent cannot meet existing clinical needs.
[0007] At present, in clinical practice, patients with highly irregular myopic astigmatism and keratoconus caused by traumatic corneal injury who need corneal stroma thickening mostly use allogeneic corneas, but due to the small number of donations, patients have a long waiting period. The clinical consensus is that artificial matrix materials need to meet the following characteristics: ① Excellent biocompatibility, rapid promotion of corneal nerve repair, and no immune rejection; ② High light transmittance, no obstruction of light entry; ③ Long-term continuous and stable function, reducing the risk of secondary surgery; ④ The material can be customized for different eye structures; ⑤ The material is inexpensive and easy to obtain. Summary of the invention
[0008] The object of the present invention is to provide a collagen-based and highly transparent matrix for corneal thickening and a preparation method thereof, so as to overcome the deficiencies in the prior art.
[0009] To achieve the above object, the present invention provides the following technical solutions: The present application discloses a method for preparing a collagen-based and highly transparent matrix for corneal thickening, comprising the following steps: S1. Preparation of substrate: The collagen composite solution is assembled into a collagen matrix implant with uniform curvature and transparency greater than 90% by electrochemical deposition on a mold with a set curvature radius of 6.8-7.8 mm; The collagen composite solution is composed of collagen, glacial acetic acid, hydrogen peroxide, heparin components and water; S2, double cross-linking: the collagen matrix implant obtained in step S1 is placed together with the mold in an EDC / NHS cross-linking agent solution with a molar concentration of 5mM to 35mM for cross-linking for 4 to 8h; after completion, the residual EDC / NHS cross-linking agent is cleaned, the collagen matrix implant is separated from the mold, and placed under a 256nm ultraviolet light source for cross-linking for 30min to 150min to obtain a double cross-linked collagen matrix implant; S3, carrying NGF, placing the double cross-linked collagen matrix implant of step S2 in the nerve growth factor solution and soaking it for 10 to 30 minutes, and obtaining the collagen-based and highly transparent matrix for corneal thickening after absorption and binding.
[0010] Preferably, step S1 includes the following sub-steps: S11, preparation of collagen composite solution: dissolving collagen in a solution containing glacial acetic acid and hydrogen peroxide, adding heparin component, stirring fully, centrifuging and degassing, to obtain collagen composite solution; S12. Construction of an electrochemical deposition assembly device: Use titanium sheets and ruthenium-iridium sheets of the same size as electrode sheets, wherein the titanium sheet is used as a cathode and the ruthenium-iridium sheet is used as an anode, and place them in parallel and overlap so that the areas of the electrode sheets completely overlap, thereby obtaining an electrochemical deposition assembly device; S13: The electrochemical deposition assembly device obtained in step S12 is immersed in the collagen composite solution obtained in step S11, and a constant current is applied to both ends of the electrode at a density of 4.10-5.50 mA / cm 2 , electrochemical deposition assembly was performed to obtain a collagen matrix graft.
[0011] Preferably, in the collagen composite solution, the concentration of collagen is 0.2wt%~0.5wt%, the mass fraction of glacial acetic acid is 1.0%~2.0% (v / v), the mass fraction of hydrogen peroxide is 8%~15% (v / v), and the heparin component is 0.1wt%~0.5wt%.
[0012] Preferably, the heparin component is one or more of heparin, heparin sodium, and heparan sulfate.
[0013] Preferably, in step S1, the electrochemical deposition assembly time is 15 to 30 minutes.
[0014] Preferably, in step S2, the mass ratio of the collagen matrix implant to the EDC / NHS solution is 1 g:60-100 ml.
[0015] Preferably, the intensity of the ultraviolet light source in step S2 is 500-1500 μw / cm 2 The distance between the ultraviolet light source and the collagen implant is 5~30cm.
[0016] Preferably, the nerve growth factor in step S3 is human recombinant nerve growth factor.
[0017] The present invention also discloses a collagen-based and highly transparent matrix for corneal thickening, which is prepared by adopting the preparation method of the collagen-based and highly transparent matrix for corneal thickening.
[0018] Beneficial effects of the present invention: 1. Compared with the traditional method of preparing samples by filling molds, the present invention adopts the electrodeposition assembly technology solution, which controls the diameter and thickness of collagen assembly fibers and arranges them in an orderly and regular manner through electric field energy regulation, thereby reducing the scattering and refraction of light and increasing the light transmittance of the cornea to more than 90%, effectively avoiding the problem of light obstruction caused by the material itself. In addition, the operation is simple, time-consuming and less traumatic when combined with femtosecond equipment.
[0019] 2. The material is based on collagen. Because it and human autologous corneal tissue are both collagen, it has excellent biocompatibility. The heparin component in the collagen matrix component can freely graft nerve growth factor (rhNGF) in its binding domain, allowing the material to release growth factors in situ, which can effectively promote the regeneration of matrix nerve fibers between corneal layers. After the nerves are dispatched, the nutrition supply to the eye is guaranteed, which is conducive to faster healing of damaged corneal matrix tissue and achieves better postoperative recovery effect.
[0020] 3. The present invention is used for corneal stroma thickening, and carries out physical and chemical double cross-linking design to significantly improve the material's resistance to enzymatic hydrolysis. Compared with polymer implant materials such as PMMA / PGA, the collagen matrix has biocompatibility while still having strong mechanical properties and anti-degradation properties. It can maintain the thickness of the corneal stroma within a certain range for a long time and prolong the time of effective service to patients.
[0021] The features and advantages of the present invention will be described in detail through embodiments in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The comparison of the enzymatic hydrolysis time of the collagen implant and the rabbit cornea in vitro in Example 1; Figure 2 It is the result of cell proliferation on the surface of the collagen implant in Example 2; Figure 3 The collagen implants were implanted into the rabbit back muscles in Example 3. Figure 4 This is the eye status of rabbits 6 months after implantation of collagen grafts between corneal layers; Figure 5 This is the OCT comparison of collagen grafts and allogeneic corneal stroma implanted between rabbit corneal stroma for 6 months; Figure 6 The results are shown in Table 1. These are the results of corneal stromal nerve repair in rabbits after interlaminar implantation of Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0023] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below through the accompanying drawings and embodiments. However, it should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the scope of the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concept of the present invention.
[0024] The present invention provides a method for preparing a collagen-based and highly transparent matrix for corneal thickening, comprising the following steps: S1. Preparation of substrate: The collagen composite solution is assembled into a collagen matrix implant with uniform curvature and transparency greater than 90% by electrochemical deposition on a mold with a set curvature radius of 6.8-7.8 mm; the collagen composite solution is composed of collagen, glacial acetic acid, hydrogen peroxide, heparin and water; wherein, in the collagen composite solution, the concentration of collagen is 0.2wt%~0.5wt%, the mass fraction of glacial acetic acid is 1.0%~2.0% (v / v), the mass fraction of hydrogen peroxide is 8%~15% (v / v), and the heparin component is 0.1wt%~0.5wt%; the electrochemical deposition assembly time is 15~30min; Specifically, step S1 includes the following sub-steps: S11, preparation of collagen composite solution: dissolving collagen in a solution containing glacial acetic acid and hydrogen peroxide, adding heparin component, stirring fully, centrifuging and degassing, to obtain collagen composite solution; S12. Construction of an electrochemical deposition assembly device: Use titanium sheets and ruthenium-iridium sheets of the same size as electrode sheets, wherein the titanium sheet is used as a cathode and the ruthenium-iridium sheet is used as an anode, and place them in parallel and overlap so that the areas of the electrode sheets completely overlap, thereby obtaining an electrochemical deposition assembly device; S13: The electrochemical deposition assembly device obtained in step S12 is immersed in the collagen composite solution obtained in step S11, and a constant current is applied to both ends of the electrode at a density of 4.10-5.50 mA / cm 2 , electrochemical deposition assembly was performed to obtain a collagen matrix graft.
[0025] S2, double cross-linking: the collagen matrix implant obtained in step S1 is placed together with the mold in an EDC / NHS cross-linking agent solution with a molar concentration of 5mM~35mM for cross-linking for 4~8h; after completion, the residual EDC / NHS cross-linking agent is cleaned, the collagen matrix implant is separated from the mold, and placed under a 256nm ultraviolet light source for cross-linking for 30min~150min to obtain a double cross-linked collagen matrix implant; specifically, the mass ratio of the collagen matrix implant to the EDC / NHS solution is 1g:60~100ml; the intensity of the ultraviolet light source is 500~1500μw / cm 2 The distance between the ultraviolet light source and the collagen implant is 5~30cm.
[0026] S3, carrying NGF, placing the double cross-linked collagen matrix implant of step S2 in the nerve growth factor solution and soaking it for 10 to 30 minutes, and obtaining the collagen-based and highly transparent matrix for corneal thickening after absorption and binding.
[0027] In a feasible embodiment, the heparin component is one or more of heparin, heparin sodium, and heparan sulfate.
[0028] In a feasible embodiment, the nerve growth factor in step S3 is human recombinant nerve growth factor.
[0029] Embodiment 1: S1. Preparation of collagen implant main substrate: S11: Dissolve collagen in 1.0% (v / v) glacial acetic acid solution, 8% (v / v) hydrogen peroxide, add heparin, heparin sodium, and heparan sulfate to make the effective mass fraction of heparin 0.5wt%, and the final concentration of collagen 0.2wt%, to obtain 1500mL solution. After fully stirring, centrifuge to degas, and precool for use.
[0030] S12: A titanium sheet of 15×15 cm and a curvature radius of 6.8 mm and a ruthenium-iridium electrode were used as the cathode and the anode, respectively, and were placed in parallel in an electrochemical deposition assembly tank (volume of 4 L) to avoid any non-overlapping parts.
[0031] S13: Pour the above collagen solution into the electrochemical deposition assembly tank along the edge, and then energize the electrodes with a current density of 5.50 mA / cm 2 , the electrodeposition assembly time is 15min.
[0032] S2. Double cross-linking of collagen implants: The collagen implants and molds were cross-linked at room temperature for 8 hours at a mass ratio of 1g collagen to 5mM EDC solution. After the demoulding, the residual EDC / NHS cross-linking agent was washed off with injection water and placed under a 256nm ultraviolet light source with an intensity of 1500μw / cm 2 The vertical height between the light source and the collagen implant was 5 cm, and the cross-linking was performed for 30 minutes.
[0033] S3. Loading with NGF: Place the collagen implant prepared in step S2 in a recombinant human nerve growth factor (rhNGF) solution in a 37°C shaker and soak for 10 minutes.
[0034] After completion, the sample was placed in a vial containing PBS solution and sterilized by irradiation to obtain a finished collagen matrix implant.
[0035] Embodiment 2: S1. Preparation of collagen implant main substrate: S11: Dissolve collagen in 2.0% (v / v) glacial acetic acid solution, 15% (v / v) hydrogen peroxide, add heparin and heparin sodium to make the effective mass fraction of heparin 0.1wt%, and the final concentration of collagen 0.5wt%, to obtain 1500mL solution. Stir thoroughly, degas by centrifugation, and precool for later use.
[0036] S12: A titanium sheet of 15×15 cm and a curvature radius of 7.8 mm and a ruthenium-iridium electrode were used as the cathode and the anode, respectively, and were placed in parallel in an electrochemical deposition assembly tank (volume of 4 L) to avoid any non-overlapping parts.
[0037] S13: Pour the above collagen solution into the electrochemical assembly tank along the edge, and then energize the electrodes with a current density of 4.10 mA / cm 2 , the electrodeposition assembly time is 30min.
[0038] S2. Double cross-linking of collagen implants: The collagen implants and molds were cross-linked for 4 hours at a mass ratio of 1g collagen to 35mM EDC solution (molar concentration: 60ml). After the demoulding, the residual EDC / NHS cross-linking agent was washed off with injection water and placed under a 256nm ultraviolet light source with an intensity of 500μw / cm 2 The vertical height between the light source and the collagen implant was 30 cm, and the cross-linking time was 150 min.
[0039] S3. Loading with NGF: Place the collagen implant prepared in step S2 in a recombinant human nerve growth factor (rhNGF) solution in a shaking incubator at 37°C and soak for 30 minutes.
[0040] Finally, the sample was placed in a vial containing PBS solution and sterilized by irradiation to obtain a finished collagen matrix implant.
[0041] Embodiment 3: S1. Preparation of collagen implant main substrate: S11: Dissolve collagen in 1.4% (v / v) glacial acetic acid solution, 10% (v / v) hydrogen peroxide, add heparin, sodium heparin, and heparan sulfate to make the effective mass fraction of heparin 0.1wt%, and the final concentration of collagen 0.3wt%, to obtain 1500mL solution. After fully stirring, centrifuge to degas, and precool for use.
[0042] S12: A titanium sheet of 15×15 cm and a curvature radius of 7.4 mm and a ruthenium-iridium electrode were used as the cathode and the anode, respectively, and were placed in parallel in an electrochemical deposition assembly tank (volume of 4 L) to avoid any non-overlapping parts.
[0043] S13: Pour the above collagen solution into the electrochemical deposition assembly tank along the edge, and then energize the electrodes with a current density of 4.10 mA / cm 2 , the electrodeposition assembly time is 30min.
[0044] S2. Double cross-linking of collagen implants: The collagen implants and molds were cross-linked for 4 hours at a mass ratio of 1g collagen to 30mM EDC solution (molar concentration: 80ml). After the demoulding, the residual EDC / NHS cross-linking agent was washed off with injection water and placed under a 256nm ultraviolet light source with an intensity of 600μw / cm 2 The vertical height between the light source and the collagen implant was 15 cm, and the cross-linking lasted for 120 min.
[0045] S3. Loading with NGF: Place the collagen implant prepared in step S2 in a recombinant human nerve growth factor (rhNGF) solution in a shaking incubator at 37°C and soak for 20 minutes.
[0046] After completion, the sample was placed in a vial containing PBS solution and sterilized by irradiation to obtain a finished collagen matrix implant.
[0047] Comparative Example 1: Comparative Example 1 is based on Example 1, and the final step of soaking heparin is adjusted, that is, Comparative Example 1 does not soak heparin components, does not carry out NGF operation, and after completing UV cross-linking, it is bottled and irradiated for sterilization. The specific steps are as follows.
[0048] S1. Preparation of collagen implant main substrate: S11: Dissolve collagen in 1.0% (v / v) glacial acetic acid solution, 8% (v / v) hydrogen peroxide, and 0.2wt% collagen to obtain 1500mL solution. Stir thoroughly, degas by centrifugation, and precool for later use.
[0049] S12: A titanium sheet of 15×15 cm and a curvature radius of 6.8 mm and a ruthenium-iridium electrode were used as the cathode and the anode, respectively, and were placed in parallel in an electrochemical deposition assembly tank (volume of 4 L) to avoid any non-overlapping parts.
[0050] S13: Pour the above collagen solution into the electrochemical assembly tank along the edge, and then energize the electrodes with a current density of 5.50 mA / cm 2 , the electrodeposition assembly time is 15min.
[0051] S2. Double cross-linking of collagen implants: The collagen implants and molds were cross-linked at room temperature for 8 hours at a mass ratio of 1g collagen to 5mM EDC solution. After the demoulding, the residual EDC / NHS cross-linking agent was washed off with injection water and placed under a 256nm ultraviolet light source with an intensity of 1500μw / cm 2 The vertical height between the light source and the collagen implant was 5 cm, and the cross-linking was performed for 30 minutes.
[0052] After completion, the samples were placed in vials containing PBS solution and sterilized by irradiation.
[0053] Comparative Example 2: Comparative Example 2 is based on Example 2, and the dual cross-linking method is adjusted. After the EDC cross-linking is completed, the residual EDC cross-linking is washed away, and no optical communication is performed, and only one cross-linking method is retained, as follows: S1. Preparation of collagen implant main substrate: S11: Dissolve collagen in 2.0% (v / v) glacial acetic acid solution, 15% (v / v) hydrogen peroxide, add heparin and heparin sodium to make the effective mass fraction of heparin 0.1wt%, and the final concentration of collagen 0.5wt%, to obtain 1500mL solution. Stir thoroughly, degas by centrifugation, and precool for later use.
[0054] S12: A titanium sheet of 15×15 cm and a curvature radius of 7.8 mm and a ruthenium-iridium electrode were used as the cathode and the anode, respectively, and were placed in parallel in an electrochemical deposition assembly tank (volume of 4 L) to avoid any non-overlapping parts.
[0055] S13: Pour the above collagen solution into the electrochemical assembly tank along the edge, and then energize the electrodes with a current density of 4.10 mA / cm 2 , the electrodeposition assembly time is 30min.
[0056] S2. Double cross-linking of collagen implants: The collagen implants and molds were cross-linked for 4 hours at a mass ratio of 1 g collagen to 35 mM EDC solution of 1 g: 60 ml. After the demoulding, the residual EDC / NHS cross-linking agent was washed off with injection water, and the photo-cross-linking step was not performed.
[0057] S3. Loading with NGF: Place the collagen implant prepared in step S2 in a recombinant human nerve growth factor (rhNGF) solution in a shaking incubator at 37°C and soak for 30 minutes.
[0058] Finally, the sample was placed in a vial containing PBS solution and sterilized by irradiation to obtain a collagen matrix implant. The results of the mechanical test comparison experiment are shown in Table 1 below.
[0059] Comparative Example 3: Comparative Example 3 is based on Example 1, but the current is increased to 6.5 mA / cm 2 , and the other parameters remain unchanged, which is used to compare and test the diameter of collagen fiber assembly and the transmittance of the finished product at a specific wavelength.
[0060] Experiment 1: Mechanical properties test of collagen matrix implants: The collagen matrix implants in Examples 1 to 3 and Comparative Example 2 were used to test mechanical properties. The samples were cut into 10×30 mm, and the tensile speed of the universal tensile machine was set to 50 mm / min. Six groups were tested in parallel for each item. As shown in Table 1, the material has a strong tensile strength, and the elastic modulus is close to that of human autologous cornea. In Comparative Example 2, only single chemical cross-linking was performed, and the tensile strength of its mechanical properties decreased by nearly 50%.
[0061] Table 1 The transmittance of the collagen matrix implants in Examples 1 to 3 and Comparative Example 3 was tested, and the transmittance of the collagen implants at 600 nm was tested using a transmittance meter, and the diameter of the collagen fibers was scanned by electron microscope. As shown in Table 2, the electric field energy continued to increase, and the degree of assembly of the collagen fibers was higher, resulting in a larger fiber diameter. Ultimately, the light caused reflection at the fibers, resulting in a decrease in transmittance.
[0062] Table 2 Transmittance test data Experiment 2: In vitro enzymatic hydrolysis test of collagen matrix implants and rabbit cornea The in vitro degradation rate of collagen matrix implants was evaluated, using rabbit cornea as a control, type I collagenase (derived from Clostridium histolyticum), and collagen matrix implants with a thickness of 200μm and a diameter of 9mm. During the test, the enzymatic solution was replaced every 8 hours to maintain enzyme activity, and the entire enzymatic process was carried out in a 37°C constant temperature water bath. In the in vitro collagenase assay, the rabbit cornea first swelled and absorbed water more violently under the attack of the enzymatic solution, which explains the increase in the residual weight of the rabbit cornea in the first 6 hours. The resistance of the double-crosslinked collagen matrix to collagenase degradation is higher than that of the rabbit cornea, see Appendix. Figure 1 The whole rabbit cornea was completely degraded in 40 hours, while the collagen matrix graft continued to degrade until 82 hours, which was twice as long as the degradation time of the rabbit cornea. Therefore, it can be seen that after the collagen matrix graft is implanted into the corneal interlayer, it can withstand the erosion of the corneal interlayer or tear enzymes for a long time.
[0063] Experiment 3: Cytotoxicity and in vitro cell proliferation test The collagen matrix implant was made into a size of 9mm in diameter, and 10ml of culture medium containing 10% fetal bovine serum was added for soaking, and cultured in an incubator at 37°C for 24h to prepare an extract for use. The L929 cells cultured in the same way were diluted, and 100ul of cell suspension was inoculated in each well of a 72-well plate, and cultured for 24h, the original culture medium was removed, and 100ul of extract was added to each well. The experimental group and the negative control group (pure cell culture medium) were taken out 48h after inoculation, and 20ul of MTT solution with a mass concentration of 5g / L was added to each well and cultured for 4h, and then the liquid in the well was removed, 150ul of DMSO was added, and the mixture was shaken on an oscillator for 10min. The absorbance value at a wavelength of 490nm was measured on an enzyme reader. The cell activity decreased by less than 15%, the cytotoxicity was low, and the stimulation to the cells was small. The results of the cell proliferation chart are attached. Figure 2 ,in Figure 2 (a) is the proliferation of cells in collagen matrix implants. Figure 2 (b) Cell proliferation in the blank group.
[0064] Experiment 4: Collagen matrix material rabbit muscle implantation test The collagen matrix implants in Example 2 were used for inflammatory response testing. The materials were cut into 1×1 cm small pieces. High-density polyethylene (HDPE) round rods were used as controls. The rabbits were anesthetized and implanted into the back muscles. Enrofloxacin was added to the drinking water one week after surgery to prevent infection. The samples were collected and observed 4 weeks after surgery. See attached. Figure 3 ,in Figure 3 a is the collagen matrix graft muscle implanted for 1 month, Figure 3 b is the control group HDPE round rod. No obvious inflammation was observed in the tissues around the collagen matrix implants, and there was no significant difference compared with the negative control HDPE, and the tissue response was even better, indicating that the collagen implants had excellent biocompatibility.
[0065] Experiment 5: Test of collagen matrix implantation into rabbit corneal stroma Six experimental rabbits were anesthetized with Zota 50 according to their body weight, and then SMILE surgery was performed on the right eye of each rabbit using Carl Zeiss femtosecond laser. Collagen grafts were implanted, and allogeneic corneal stroma was implanted in the left eye as a control. The thickness of the corneal cap was 100-130 μm, the diameter of the corneal cap was 6.5 mm, the side cutting angle was 90°, the side incision length was 3 mm, and 180 μm thick native stroma tissue was removed. After the laser scanning was completed, the negative pressure suction was removed, the corneal side incision was separated, and the anterior and posterior surfaces of the native stroma tissue were separated and removed in sequence. Finally, it was removed from the side incision, and the collagen matrix graft with a diameter of 6 mm and a thickness of 180 μm was inserted into the capsular bag with forceps without suturing. The left eye control used allogeneic corneal stroma, that is, the corneal stroma removed from another rabbit was implanted between the corneal layers, and the parameters were consistent with the right eye. After surgery, corneal bandage glasses were worn, and routine antibiotics and hormone eye drops were used for postoperative care 3 to 4 times a day. After 4 weeks, the frequency was gradually reduced. The ocular status of the animals was observed 6 months after surgery. Figure 4 , OCT see attached Figure 5 ,in Figure 5 The a is 6 months of allogeneic interlaminar transplantation; Figure 5 b is the interlayer transplantation of collagen matrix grafts at 6 months.
[0066] Experiment 6: Corneal stromal nerve repair test Based on the animal experiment of Experiment 5, samples were collected at 2 weeks and the corneal stromal nerves were stained and tested. Before sampling, permeabilization buffer (1% Triton-X100 in 1×PBS) was prepared and the buffer was kept at 4°C. It should be noted that the dilution of paraformaldehyde: it is recommended to dilute from 16% paraformaldehyde solution without methanol, because methanol can permeabilize the cell membrane and affect the morphology of cell structures such as the actin cytoskeleton, which is not conducive to observation. After sampling, the staining operation was started as soon as possible. The growth of the corneal stromal nerve fibers of the 2-week rabbit is shown in the attached figure. Figure 6 ,in Figure 6 a is 14 days after implantation, the matrix layer nerve fibers resumed growth, Figure 6 b is the control group without heparin in comparative example 1; it can be seen that in the experimental group with rhNGF implants, the corneal stroma layer has more fine fibers growing at the ends of the thick fibers that were broken due to surgery. In the control group without rhNGF, no obvious fine fibers grew at the ends of the nerves, and the nerve repair effect was significantly worse than that of the experimental group. This suggests that the nerve growth factor absorbed in the collagen implant can promote the rapid repair of nerve fibers after being implanted in situ in the stroma layer.
[0067] The present invention provides a method for preparing a collagen matrix implant using an electrochemical deposition assembly device and a collagen solution as a substrate. The method controls the diameter and thickness of collagen assembly fibers and arranges them in an orderly and regular manner through electric field energy regulation, thereby reducing light scattering and refraction and increasing the light transmittance of the collagen matrix implant. The method can be customized for different eye structures, has high preparation efficiency, simple process operation, and is suitable for large-scale production.
[0068] Collagen has excellent biocompatibility. On this basis, the heparin component in the collagen solution enables it to autonomously bind to the nerve growth factor in the human nerve growth factor (rhNGF) solution, and slowly releases it in situ to promote nerve repair and accelerate the fusion and matching of the collagen implant and the matrix layer. Uncross-linked collagen materials have poor swelling and resistance to enzymatic hydrolysis. At the same time, excessive swelling can cause corneal nerve compression and increase discomfort, and poor resistance to enzymatic hydrolysis can cause the material morphology to be unable to maintain. Therefore, a targeted double cross-linking design is carried out to significantly improve the mechanical properties and resistance to enzymatic hydrolysis of the collagen implant and reduce its swelling degree, thereby reducing surgical risks and providing longer-term services for patients.
[0069] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a collagen-based and highly transparent matrix for corneal thickening, characterized in that: The steps include: S1. Preparation of substrate: The collagen composite solution is assembled into a collagen matrix implant with uniform curvature and transparency greater than 90% by electrochemical deposition on a mold with a curvature radius of 6.8-7.8 mm; The collagen composite solution is composed of collagen, glacial acetic acid, hydrogen peroxide, heparin components and water; S2, double cross-linking: the collagen matrix implant obtained in step S1 is placed together with the mold in an EDC / NHS cross-linking agent solution with a molar concentration of 5mM to 35mM for cross-linking for 4 to 8h; after completion, the residual EDC / NHS cross-linking agent is cleaned, the collagen matrix implant is separated from the mold, and placed under a 256nm ultraviolet light source for cross-linking for 30min to 150min to obtain a double cross-linked collagen matrix implant; S3, carrying NGF, placing the double cross-linked collagen matrix implant of step S2 in the nerve growth factor solution and soaking it for 10 to 30 minutes, and obtaining the collagen-based and highly transparent matrix for corneal thickening after absorption and binding.
2. The method for preparing a collagen-based and highly transparent matrix for corneal thickening according to claim 1, characterized in that: Step S1 includes the following sub-steps: S11, preparation of collagen composite solution: dissolving collagen in a solution containing glacial acetic acid and hydrogen peroxide, adding heparin component, stirring fully, centrifuging and degassing, to obtain collagen composite solution; S12. Construction of an electrochemical deposition assembly device: Use titanium sheets and ruthenium-iridium sheets of the same size as electrode sheets, wherein the titanium sheet is used as a cathode and the ruthenium-iridium sheet is used as an anode, and place them in parallel and overlap so that the areas of the electrode sheets completely overlap, thereby obtaining an electrochemical deposition assembly device; S13: The electrochemical deposition assembly device obtained in step S12 is immersed in the collagen composite solution obtained in step S11, and a constant current is applied to both ends of the electrode with a density of 4.10-5.50 mA / cm 2 , electrochemical deposition assembly was performed to obtain a collagen matrix graft.
3. The method for preparing a collagen-based and highly transparent matrix for corneal thickening according to claim 1, characterized in that: In the collagen composite solution, the concentration of collagen is 0.2wt%~0.5wt%, the mass fraction of glacial acetic acid is 1.0%~2.0% (v / v), the mass fraction of hydrogen peroxide is 8%~15% (v / v), and the heparin component is 0.1wt%~0.5wt%.
4. A method for preparing a collagen-based and highly transparent matrix for corneal thickening as claimed in claim 1, characterized in that: The heparin component is one or more of heparin, heparin sodium, and heparan sulfate.
5. The method for preparing a collagen-based and highly transparent matrix for corneal thickening according to claim 1, characterized in that: In step S1, the electrochemical deposition assembly time is 15 to 30 minutes.
6. The method for preparing a collagen-based and highly transparent matrix for corneal thickening according to claim 1, characterized in that: In step S2, the mass ratio of the collagen matrix implant to the EDC / NHS solution is 1 g: 60-100 ml.
7. The method for preparing a collagen-based and highly transparent matrix for corneal thickening according to claim 1, characterized in that: The intensity of the ultraviolet light source in step S2 is 500~1500μw / cm 2 The distance between the ultraviolet light source and the collagen implant is 5~30cm.
8. The method for preparing a collagen-based and highly transparent matrix for corneal thickening according to claim 1, characterized in that: In step S3, the nerve growth factor is human recombinant nerve growth factor.
9. A collagen-based and highly transparent matrix for corneal thickening, characterized in that: The corneal thickening matrix is prepared by the method for preparing a collagen-based and highly transparent matrix for corneal thickening as described in any one of claims 1 to 8.
Citation Information
Patent Citations
A composite collagen hydrogel material, an implantable ophthalmic device comprising such material and methods of producing the composite collagen hydrogel material and the implantable ophtalmic device
CN108601861A
Production method of transplanting material
CN1460715A
High-strength bionic collagen membrane and preparation method thereof
CN104857561A
Nerve scaffold for nerve injury repairing and preparing method and application thereof
CN105597148A
Active amniotic membrane material loaded with growth factors and preparation method thereof
CN111450327A
Cited By
Preparation method of bionic cornea stroma lens capable of being used for refractive correction
CN120754321A
Collagen membrane material capable of stably existing in body for long time and preparation method of collagen membrane material
CN121177582A